The research needs of an ICM trainee: The RAFT national survey results and initiatives to improve trainee research opportunities. (May 2017) - Shaw, Michelle; Harris, Benjamin; Bonner, Stephen
Research is key to intensive care practice but it is not certain whether trainees get the research experience they want to prepare them for clinical practice as consultants. We distributed a survey via Research & Audit Federation of Trainees to 478 current intensive care medicine trainees to establish their views. We restricted analysis to regions with an 80% or greater response rate ( n = 235 responses) to reduce self-selection bias. Our results indicated that the desire for research activities was high but multiple barriers exist. We suggest simple initiatives combined with engagement of trainee research networks and local Clinical Research Networks to improve trainee access to research opportunities. Greater freedom to participate in research activities could be created by broader ARCP clinical governance requirements, flexible interpretation of the FICM curriculum and support of trainees wishing to use their non-clinical time for projects. A resource detailing local research activity and appropriate contacts could help trainees plan suitable activities.